The adult learner the definitive classic in adult education and human resource development - Knowles, Malcolm S. (Malcolm Shepherd) 1913-1997.; Holton, Elwood F. 1957-; Swanson, Richard A. 1942- (Amsterdam Boston Elsevier, 2005)
"The Adult Learner, Sixth Edition is essential reading for adult learning practitioners, students and HRD professionals. It provides a theoretical framework for understanding the adult learning issues both in the teaching and workplace environments."--BOOK JACKET.
Ch. 1. Introduction -- Ch. 2. Exploring the world of learning theory -- Ch. 3. Theories of learning -- Ch. 4. A theory of adult learning : andragogy -- Ch. 5. Theories of teaching -- Ch. 6. An andragogical process model for learning -- Ch. 7. Andragogy in practice -- Ch. 8. Adult learning within human resource development -- Ch. 9. New perspectives on andragogy -- Ch. 10. Beyond andragogy -- Ch. 11. The future of andragogy -- Ch. 12. Whole-part-whole learning model -- Ch. 13. From teacher to facilitator of learning -- Ch. 14. Making things happen by releasing the energy of others -- Ch. 15. Some guidelines for the use of learning contracts -- Ch. 16. Core competency diagnostic and planning guide -- Ch. 17. Personal adult learning style inventory -- Ch. 18. Training delivery problems and solutions -- Ch. 19. A model for developing employee work effectiveness in new roles and environments.
Formerly CIP.
Keywords: Adult learning; Adult education; Training